Knowledge Mapping Bidang Ilmu Perpustakaan Dengan Metode Nine Basics of Information Science - Zeni Istiqomah; Amalia Nurma Dewi; Heri Suwignyo (Pustakaloka, 2021)
The purpose of this study is to analyze the knowledge of mapping in the field of Library Science with the Nine Basics of Information Science method and to analyze the development that has led to the Kemenristekdikti nomenclature. The research method used is quantitative research with a survey approach. The total population of 1,597 and a sample of 94. he validity test used construct validity and empirical reliability tests. Data analysis with mean analysis based on variables from all respondents and presented. The results showed that of the knowledge mapping the field of library science was categorized into three categories, namely the category of foundation, resources, and subject-based knowledge. he category of foundation shows that the use of theory used has varied, but it was found that several publications did not use theory. The method of publication is more inclined to use qualitative methods, and a relatively high level of sophistication publication. The category of resources is more inclined to use secondary information sources. The category of subject-based knowledge tends to be the subject of social issues, the subject of the technique and process of presenting information in the library, the subject of systems and application development, and the subject of technology. The results of the knowledge mapping in the field of library science in the publications on the Garuda website have also led to a new nomenclature, which is more directed at the field of social issues. Keywords: knowledge mapping, library science , library science and information science